PERAN FINANCIAL TECHNOLOGY DALAM MENINGKATKAN KINERJA PERBANKAN SYARIAH DI INDONESIA - Hasni Hasni (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2022)
This research aims to test and analyze the role of Financial technology in Improving the Performance of Islamic Banking in Indonesia, the object of research on Islamic Commercial Banks (BUS) using financial performance report data available at the Financial Services Authority for 2018-2021. By using the variables of the number ofusers financial technology, the number oftransactions financial technology and the number ofassets financial technology on the financial performance of Islamic banks. The test used is the research method explanative, Data analysis using multiple linear regression analysis, from the results of this study it is known that the number of users of financial technology and the number of transactions of financial technology have a positive influence on the performance of Islamic banks, this is because many banks that have collaborated with financial technology have increased performance every year, both from the bank and the company, financial technology while the number ofassets financial technology has no effect on the performance of Islamic banks. This is because there are still some bank industries that have not collaborated with financial technology for fear of the negative impacts that arise when collaborating with financial technology, such as the occurrence hackers of personal data and soon.